PERTUMBUHAN TANAMAN GAHARU Aquilaria spp DENGAN PEMBERIAN MIKORIZA DAN MULSA PADA LAHAN TERBUKA DI TANAH ULTISOL - Nurbaiti, Siti; Muin, Abdurrani; Fahrizal, M (JURNAL HUTAN LESTARI, 2016)
Agarwood (Aquilaria spp) only can be grown under shade on the first phase of planting because this plant has silvic semi tolerance. This condition make agarwood difficult to grow under open field. Due to this condition, to grow in open field, arbuscular mycorrhizal fungi and mulching are needed. The research work aimed to find the effect of mycorrhizal fungi and mulching on agarwood growth in open field. The research work was conducted in experiment garden of Universitas Tanjungpura in Pak Laheng village, Toho district, Mempawah regency until the plant aged 8 weeks. The research work employed split plot design using a randomized block design. The treatment consisted of main factor with seedling without fungi (A1) and seedling with fungi (A2) and additional factor with plant without mulching (B1) and plant with mulching (B2). The research findings showed that in the age 8 weeks the mycorrhizal fungi only could fasten the growth of diameter and while mulching had effect on height, diameter and number of leaves. The interaction of these two treatment gave significant impact on diameter and number of leaves. Keywords : Aquilaria spp, Arbuscular Mycorrhizal Fungi and Mulching, Open Field and Ultisol Soil